2017
DOI: 10.29252/nrip.irj.15.4.377
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Needs Assessment Study and Deployment of QFD Targeted at New Wheelchair Design

Abstract: Objectives: Extensive use of wheelchair increases caregiver dependency, risk of bedsores, risk of injury during transfer, and so on, and it effectively decreases quality of life, safety, and comfort of the people with disability. Therefore, improving the design of wheelchairs is highly essential in promoting the quality of life and level of participation among people with disability. The design of wheelchair for users of a developed country might be inadequate in comparison to a developing country such as Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…These individuals often lack independent mobility and depend on a helping person to push them in a manual wheelchair. To accommodate this population, several researchers have used technologies originally developed for mobile robots to create smart wheelchairs [5,6]. A smart wheelchair typically consists of either a standard power wheelchair to which a computer and a set of sensors are added or a mobile robot base to which a seat is attached.…”
Section: Discussionmentioning
confidence: 99%
“…These individuals often lack independent mobility and depend on a helping person to push them in a manual wheelchair. To accommodate this population, several researchers have used technologies originally developed for mobile robots to create smart wheelchairs [5,6]. A smart wheelchair typically consists of either a standard power wheelchair to which a computer and a set of sensors are added or a mobile robot base to which a seat is attached.…”
Section: Discussionmentioning
confidence: 99%
“…Due to prolonged seated posture with being inactive in wheelchair, these subjects are exposed to many physical and psychological health problems e.g., fatigue, pain in the hip joint, bedsores, etc. Comprehensive needs assessment study of wheelchair users [3] reported several common problems such as (1) difficulties in transfer from a wheelchair to and from bed (2) problems to stand from seating position (3) problems in using commode without help and (4) risk of pressure sores due to extensive use of a wheelchair. Aforementioned issues can be resolved by designing and developing a reconfigurable wheelchair, so that it can meet practical demands of the extensive wheelchair users.…”
Section: Identification Of Contradictionmentioning
confidence: 99%
“…Comprehensive needs assessment study of extensive wheelchair users [3] reported several common problems such as (1) difficulties in transfer from a wheelchair to and from bed (2) difficulties in stand from seating position (3) difficulties using commode without caregiver support and (4) risk of pressure sores due to extensive use of a wheelchair. A wheelchair with back seat adjustment can assist extensive wheelchair users in health preservation, balancing, trunk positioning, etc [4].…”
Section: Introductionmentioning
confidence: 99%